Expanding the Jurisdiction of the International Criminal Court - Prihandono, Iman; Yuniarti, Dewi Santoso (Brawijaya Law Journal, 2022)
Environmental destruction and exploitation of natural resources are some of the main causes of humanitarian conflicts, which are often international in scale. One instance was the crime of genocide conducted by Al-Bashir, which was triggered by exploitation of natural resources (resource war), causing pollution of vital water sources, and ending with conflict in Darfur, Sudan. This case is evidence that environmental destruction can be a driving factor for crimes against humanity. In response to this, the International Criminal Court (ICC) issued a Policy Paper, which sets out considerations to prosecute cases of environmental destruction and illegal exploitation of natural resources, which is referred to by some as ecocide. With growing demand of the international community, not only natural persons, but corporations are urged to be prosecuted before the ICC for ecocide. This research is normative legal research. It is intended to outline the current rise of demand for the ICC to prosecute cases of ecocide, whilst challenging the existing jurisdiction of the ICC based on the Rome Statute. This paper will discuss whether the ICC have jurisdiction to adjudicate ecocide, expanding the Court’s jurisdiction to prosecute corporations, and crimes conducted in and/or by citizens of States that are not members of the Rome Statute, such as Indonesia. This paper concludes with constructive recommendations for businesses to start re-evaluating their business plans to put environment and human rights awareness into priority concern.